Unusual Case of Midline Middle Skull Base Lymphoma Mimicking as Invasive Pituitary Adenoma - Naik, Harish; Survashe, Pravin; Velho, Vernon; Bhide, Anuj; Bhople, Laxmikant; Guha, Amrita (Indian Journal of Neurosurgery, 2018)
Non-Hodgkin's lymphoma (NHL) is a rare tumor of the skull base. As the incidence of primary central nervous system (CNS) lymphoma has increased, atypical presentations involving the skull base are being reported. However, isolated involvement of middle skull base, that too predominantly the clivus and parasellar region, is rarely seen. We present a case of middle-age woman with midline skull base lesion located in the sella with invasion of the ventral part of upper part of clivus (posterior clinoid) and also the parasellar region causing involvement of optic and abducens nerve with preserved hormonal functions. She was operated endoscopically for partial resection of the lesion. Histopathology turned out to be non-Hodgkin's lymphoma of NK/T-cell variety. So far NK/T-cell lymphoma of the sella with invasion into the clivus has never been reported in literature to the best of our knowledge.
Keywords: non-Hodgkin's lymphoma; NK/T-cell clival lymphoma